Oral Health Consequences of Use of Smokeless Tobacco in North India: A Cross-Sectional Survey - Agrawal, Neha; Aggarwal, Anshul; Gupta, Narinder Dev; Tewari, Rajendra Kumar; Gupta, Juhi; Garg, Amit Kumar (Pesquisa brasileira em odontopediatria e clínica integrada, 2021)
ABSTRACT Objective: To evaluate the effects of commonly used smokeless tobacco forms on oral health at habitual placement sites of smokeless tobacco compared to non-placement sites among the North Indian population. Material and Methods: This cross-sectional study was conducted among 542 individuals using smokeless tobacco recruited from the outpatient wing of the Dental College. Subjects completed a questionnaire and received an oral examination. Periodontal pocket depth, gingival index, plaque index, gingival recession, and oral mucosal changes were assessed. Kendal’s Tau test, paired t-test, and chi-square test were carried out to compare different variables among placement and non-placement sites. Results: Most of the subjects were male, reporting an average of 11.26 years of SLT use. Clinical inflammation of gingiva was significantly greater (p=0.01) at placement-sites (1.64 ± 0.53) of SLT in comparison to non-placement-sites (1.40 ± 0.41). The difference in the GR and PPD at placement and non-placement-sites was also statistically significant with p=0.002 and p=0.001, respectively. Clinically, the majority of subjects had mucosal changes at the placement sites, and a statistically significant association (p=0.034) was observed between the duration of the use of smokeless tobacco and the mucosal changes. Conclusion: Smokeless tobacco use predisposes to increased risk of periodontal diseases and oral mucosal changes at the placement sites in an individual due to the local irritant effect.